(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Acute cerebral ischemia (ischemic stroke) triggers systemic neuroendocrine responses that commonly alter thyroid and parathyroid physiology. The most consistent thyroid pattern is the “non-thyroidal illness syndrome” (NTIS, or low-T3 syndrome) characterized by reduced peripheral T3, variable T4, raised reverse T3 (rT3), and typically normal or low-normal TSH. These changes correlate with stroke severity and worse outcomes in many studies. Changes in parathyroid function and mineral metabolism—principally altered parathyroid hormone (PTH), vitamin D status, and calcium—have also been reported; elevated PTH and low 25-OH vitamin D associate with increased stroke risk and with particular stroke subtypes in some cohorts. This article reviews the physiology, proposed mechanisms, human and animal evidence, clinical significance, and potential implications for management and research.